Wavelength-switchable fiber laser based on few-mode fiber filter with core-offset structure. (July 2016) - Qi, Yanhui; Kang, Zexin; Sun, Jiang; Ma, Lin; Jin, Wenxing; Lian, Yudong; Jian, Shuisheng
Abstract: We propose a wavelength-switchable erbium-doped fiber ring laser based on the few-mode fiber filter with core-offset structure. The filter is constructed by splicing a section of few-mode fiber with two segments of single mode fiber. Meanwhile, the excited modes are effectively selected by controlling the core-offset splicing carefully. The novel filter is based on the interference between fundamental mode and LP 11 mode. The single-, dual-, triple- and quad-wavelength fiber laser is accomplished by adjusting the states of polarization controller at room temperature. The principle of operation is mainly based on the saturated spectral hole-burning effect and the balance between the gain and loss in the cavity. Highlights: Proposed a novel filter with core-offset structure based on few-mode fiber. The excited modes are effectively selected by controlling the core-offset splicing. A comb filter is achieved in the experiment. The single-, dual-, trial- and quad-wavelength switchable fiber laser is accomplished.